Proposal of an Evaluation System for Monitoring Suppliers and Controlling Risks in the Hospital Sector - Kaoutar JENOUI; Abdellah ABOUABDELLAH (International Journal of Supply Chain Management, 2017)
Today, the control of the purchasing function becomes a strategic tool of any hospital. Hence, hospitals are invited to create immediate value from identification and mitigation of risks in the upstream supply chain management. Among the problems encountered in the management of this chain are the evaluation and the monitoring of the performance of suppliers. The classification of the best-performing suppliers must be based on the analysis of risks that a hospital encounters when dealing with a supplier. Most experiments measure the risk according to the combination of two parameters, gravity and probability. Although these two parameters are subjectively determined, this implies the uncertainty and the imprecision of the risk value. Therefore, this paper presents an alternative approach for tackling such a problem starting with proposing a new system of evaluating suppliers, whose results will help to calculate objectively the risk associated to suppliers. Our paper is composed of four parts. The first one presents the literature review, while the second and third parts deal with the problematic definition and the proposed solution respectively, which are illustrated and validated through a case study in the fourth part. Finally, we conclude the paper with work perspectives.